Thermal processing of hydrocarbons : petroleum to petrochemicals - Banerjee, Dwijen K. (PennWell, 2019)
"This book is a must-read for the latest generation of scientists, engineers, and researchers in the petroleum industry. The product of over four decades of research, experience, and study by Dr. Dwijen Banerjee, Dr. Banerjee carefully preserves the history of the thermal processing of hydrocracking, giving credit to the pioneering scientists and discoverers of the process. In this first-of-its-kind book, the author summarizes and systematically leads readers through all aspects of the thermal cracking processes from the research laboratory to the commercial applications of the petrochemical industry. Fossil fuels consist of a continuous series of hydrocarbons mainly divided into (i) natural gas (C1-C4), (ii) conventional crude oil (C5-C40) and (iii) heavy oil / bitumen (>C40). This book discusses thermal processing of hydrocarbons - with a special emphasis on lighter hydrocarbons - whose main source is shale gas and tight oil that's recently been made abundant through fracking technology. This book details many technical parameters involved in the choosing a process when considering the type of feedstocks; operating conditions; selectivity of the desired product; the market to be targeted; and the environmental regulations to be met while also considering the economic parameters such as the investment and profit margin that govern the final choice"--